DEPRESION IN ABUSED WOMEN: RELATIONSHIP WITH PERSONALITY STYLES, CONTEXTUAL AND SITUATIONAL VIOLENCE VARIABLES - Patró Hernández, Rosa; Corbalán Berná, Francisco Javier; Limiñana Gras, Rosa María (Anales de Psicología / Annals of Psychology, 2007)
The goal of this study is examine the contribution of personality variables on the pychological impact of maltreatment experience and to identify personality styles associated with the level of depressive sympto-matology, assessment with Beck Depresion Inventory (Beck, Rush, Shaw & Emery, 1979) in a sample of 105 abused women by the partner resident in shelter centres. In this way, we have used the Millon Inventory of Per-sonality Styles (MIPS) (Millon, 1994) and measurements of violence situa-tion, aditional stressors and social support. The results showed that the level of evaluated symptoms was significantly correlated with the MIPS scales scores, after the effect of contextual and situational variables was controlled, supporting their influence on the psychological impact of maltreatment experience. Finally, MIPS scales associated with a major and minor level of depressive symptomatology was examined.